1995
DOI: 10.1159/000106960
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Malignant Lymphomatosis: A Cause of Subacute Dementia

Abstract: Intravascular malignant lymphomatosis (IML) is a rare disease characterized by proliferation of neoplastic cells of lymphoid origin within small blood vessels. The median survival of IML patients is only 6 months. Any organ can be affected, with or without clinical expression. Although skin lesions are classic, they are relatively uncommon (28%). Neurological symptomatology (which evolves over a few weeks) is the most common clinical expression (83%). Dementia is the most common neurological symptom that occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…IVL has been confused with other possible conditions including vasculitis, dementia, or infarction, occult neoplasm, and infection. When the lungs are involved, patients experience shortness of breath, hypoxemia, and, rarely, pulmonary hypertension, and the disease may simulate various lung diseases, particularly diffuse interstitial lung disease or a subacute or chronic infectious condition (6,7). Moreover, due to the rarity of this condition, ready diagnosis of the disease is difficult, and lung lesions in patients with IVL are often detected at autopsy (8).…”
Section: Study Patientsmentioning
confidence: 99%
“…IVL has been confused with other possible conditions including vasculitis, dementia, or infarction, occult neoplasm, and infection. When the lungs are involved, patients experience shortness of breath, hypoxemia, and, rarely, pulmonary hypertension, and the disease may simulate various lung diseases, particularly diffuse interstitial lung disease or a subacute or chronic infectious condition (6,7). Moreover, due to the rarity of this condition, ready diagnosis of the disease is difficult, and lung lesions in patients with IVL are often detected at autopsy (8).…”
Section: Study Patientsmentioning
confidence: 99%
“…Regarding the occurrence of seizures associated with IVL, epileptic seizures have been reported in 8.8–25% patients with IVL [4, 5, 6]. Epileptic seizures in patients with IVL reportedly occur at a more advanced stage in most cases [6, 7]; however, patients suffering from epileptic seizures at IVL onset have also been reported [4, 6, 8, 9]. Case reports and literature reviews have shown that epileptic seizures as the first manifestation of IVL are found in 3–4% patients with IVL [4, 6].…”
Section: Discussionmentioning
confidence: 99%
“…Epileptic seizures in patients with IVL reportedly occur at a more advanced stage in most cases [6, 7]; however, patients suffering from epileptic seizures at IVL onset have also been reported [4, 6, 8, 9]. Case reports and literature reviews have shown that epileptic seizures as the first manifestation of IVL are found in 3–4% patients with IVL [4, 6]. However, IVL initially presenting as SE has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that greater than 80% of patients diagnosed with intravascular lymphomatosis presented with neurological involvement, and half of those with CNS involvement presented with signs of dementia. 10 CNS involvement is associated with a poor prognosis. 10 Our patient typified the mean age of onset and neurological involvement, but lacked any skin findings.…”
Section: Discussionmentioning
confidence: 99%